FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS PELAYANAN ADMINISTRASI PADA KANTOR KELURAHAN PULANG PISAU - Pasaribu, Muhammad Irvan Yazid Azhar (Jurnal Riset Akuntansi Politala, 2024)
Public service is an activity carried out in order to fulfill basic needs in accordance with the basic rights of every citizen for an administrative service provided by a service provider related to the public interest. The purpose of this article is to determine the factors that influence the quality of administrative services and the role of the village government in improving the quality of services to the community at the Pulang Pisau Village Office as one of the government agencies that has the authority to provide services. Research using qualitative methods that emphasize the analysis of inductive thinking processes with the dynamics of the relationship between observed phenomena and always using scientific logic. The results of the study show the quality of administrative services at the Pulang Pisau Village Office using the five indicators of the SERVQYAL (Service Quality) model, only one indicator that works well is reliability. This is due to the accuracy of officers, clear service standards and the ability of officers to use aids and officer expertise. However, four indicators that are still not running well are Physical Evidence (Tangible) the quality of service is still low due to the discomfort of the service location and the discipline of service officers, Response (Responsiveness) that officers in the service process are not smooth and timely, Guarantee (Assurance) there are still costs for bureaucracy in service. And empathy (Emparthy) prioritizes personal interests over the interests of service users.